The Constitutional Will In Human Rights Protection For Refugees - Agustine, Oly Viana (Constitutional Review, 2017)
Human rights protection granted to refugees in Indonesia has not received serious attention, in particular for those who are included in the cross-border refugees. This issue is a question of how the Constitution mandates a protection to them, whether it is an obligation of the government of Indonesia or it is volunteerism alone. The provisians are addressed in Article 28A, Article 28B paragraph (2), Article 28D paragraph (4), Article 28E paragraph (1), Article 28G paragraph (2), and Article 28H paragraph (1), and Article 28J paragraph (1), Broadly speaking, the Indonesian constitution calls for better protection of refugees to internally displaced persons and refugees across borders. This is reflected in several articles in the 1945 Constitution that mention the word âeveryoneâ in the subject which meant regardless of citizenship status or population. This is certainly in line with the values of human rights that have been recognized along with the universality of human rights that are applicable. Therefors the will of the constitution on refugees needs to be implemented in legislation in Indonesia, which describes in details the human rights protection to internally displaced persons and refugees state that the will of the constitution in the protection of human rights to refugees be implemented correctly.